Peran Pemberdayaan Kesejahteraan Keluarga (PKK) dalam Mengimplementasikan Nilai-nilai Pancasila terhadap Anggota PKK di Nagari Tanjung Kecamatan Koto VII Kabupaten Sijunjung - Amelia, Delvira Yusti; Azwar, Azwar; Rahmat, Indra (Lembaga Yasin AlSys, 2023)
This study aims to identify and describe the implementation of Pancasila values in PKK activities for PKK members and the factors that influence the implementation of Pancasila values in PKK activities in Nagari Tanjung, Koto VII District, Sijunjung Regency. The method used in this research is descriptive qualitative with the research location in Nagari Tanjung, Koto VII District, Sijunjung Regency. The informants in this study were the management of the PKK organization, Wali Nagari, clerics, bundo kanduang, the community and members of the PKK. Data collection techniques are through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results showed that: The form of practicing Pancasila values in the PKK group at sfirst line,There is a relationship between humans and the Creator. The first implementation of the precepts was carried out by the PKK by holding a wirid once a month, there were tambourine competitions, halal bihalal and sometimes lectures.Second implementation , the relationship between humans and humans. With the cooperation of the PKK and the local Puskesmas so that the community gets good health services. Implementation of third namely the existence of activities that have been programmed every year. Then implementation of fourth there are meetings and deliberations held every month.Fifth implementation ,the existence of the value of justice can be seen from the form of assistance provided to the community. There are several factors that support and hinder the practice of Pancasila values in PKK activities in Nagari Tanjung. Factors supporting the practice of Pancasila values, namely,support from PKK members, from family, community and Nagari Government.The inhibiting factors for PKK are economic and social factors. Based on the results of the research above, it can be concluded that the form of practicing Pancasila values in the PKK group in the first precept is that there is a relationship between humans and the creator. The second principle is the relationship between humans and humans. The third precept is the attitude of love for the motherland. The fourth precept is the value of society, deliberation and democracy. The fifth precept is the value of justice. The supporting factors for the PKK are PKK members, family, community and the Nagari Government. Inhibiting factors caused by economic and social factors.